Designing a Model of Effective Factors on Creative Cultural Industries in Iran - Abbas Ghaedamini Harouni; Mehrdad Sadeghi Deh Cheshmeh; Sadegh Sadeghi Deh Cheshmeh; Narjes Mohsenifar (مدیریت نوآوری و راهبردهای عملیاتی)
Purpose: This study aimed to design a model of influential factors in creative cultural industries in Iran.Methodology: The research method is mixed (quantitative-qualitative). The statistical population of this study included experts and professors. In the Delphi section, 108 experts were used to identify 108 experts using purposive-judgmental sampling methods, and in the expert modelling section of the Ministry of Cultural Heritage, Tourism and Handicrafts, which was about 10,000 people. According to Krejcie and Morgan's table, a simple stratified method was used to select a sample size of 384 people. The Delphi questionnaire was used to identify the factors, and the researcher-made questionnaire was used for modelling. Both validity questionnaires were confirmed, and Cronbach's alpha coefficient measured its reliability above 0.70.Findings: The Delphi identification test was used to identify the influential factors and was screened in two stages. Finally, the experts identified the criteria gathered in the research background in 6 criteria and 16 sub-criteria affecting the creative cultural industries in 7 main criteria, and 17 sub-criteria were agreed upon. Also, the results of exploratory factor analysis were confirmed with the help of the information obtained from a questionnaire provided to experts and modelled with structural equations and LISREL software. These factors were ranked, and the criteria' importance from the first to the third were structural and human capital, required infrastructure, and government support.Originality/Value: By generating new needs, creative cultural industries can produce new cultural consumers and increase cultural accumulation, which requires promoting cultural capital in society by intensifying cultural uses. Therefore, a model of influential factors in creative cultural industries should be designed to produce new value audiences, properly use knowledge and technology, and act purposefully to create cultural products and services.